The teaching of anatomy throughout the centuries: From Herophilus to plastination and beyond - Papa, V.; Varotto, E.; Vaccarezza, Mauro; Ballestriero, R.; Tafuri, D.; Galassi, F.M. (2019)
© Mattioli 1885. Cultural changes, scientific progress, and new trends in medical education have modified the role of dissection in the teaching of anatomy in today's medical schools. Dissection is indispensable for a correct and complete knowledge of human anatomy, which can ensure safe as well as efficient clinical practice and the human dissection lab could possibly be the ideal place to cultivate humanistic qualities among future physicians. In this manuscript, we discuss the role of dissection itself, the value of which has been under debate for the last 30 years; furthermore, we attempt to focus on the way in which anatomy knowledge was delivered throughout the centuries, from the ancient times, through the Middles Ages to the present. Finally, we document the rise of plastination as a new trend in anatomy education both in medical and non-medical practice.